JURIDICAL REVIEW OF THE IMPLEMENTATION OF THE PRINCIPLES OF JUSTICE IN JUDGES' DECISIONS IN LAND DISPUTE CASES - Rolando Marpaung; Micael Jeriko Damanik; Parlindungan Purba; Elfrida Feronika (Journal of International Islamic Law, Human Right and Public Policy, 2023)
Land disputes are disputes that arise due to conflicts of interest over land. Land disputes cannot be avoided nowadays. This requires improvements in the field of planning and use of land for the welfare of society and most importantly legal certainty therein. The government has made various efforts to resolve land disputes quickly in order to avoid the accumulation of land disputes, which can be detrimental to the community because the land cannot be used because the land is in dispute1. Legal resolution efforts regarding land disputes or disputes are regulated in Presidential Decree no. 20/2015 concerning the National Land Agency (BPN) Article 3 points 3 and 4 states that the Head of BPN has the task of carrying out policies in the field of determining land rights, land registration and community empowerment as well as in the field of regulating, structuring and controlling land policy.